Why not teach medicine how we practice? (1999)
Teaching University hospitals need to increase their productivity and efficiency in order to survive. Ambulatory care in teaching hospitals is slower, compared to others because the academic system promotes o requires students to do lengthy medical histories and physicals, although this is not common in medical practice. In addition, the predictive values of many diagnostic tools, including parts of the Clinical history and exam, suggest that most procedures are an inefficient use of resources. To improve efficiency, students should be taught to do medical histories and physicals, with the hypothetical-deductive strategy, as clinicians do in their everyday practice.